Examining the evidence of microfinance on non-communicable disease health indicators and outcomes: A systematic literature review. Issue 2 (1st February 2022) - Fernando, Gabriela; Durham, Jo; Vlack, Sue; Townsend, Nick; Wickramasinghe, Kremlin; Gouda, Hebe
ABSTRACT: Microfinance has emerged as an effective approach to address health outcomes, particularly infectious diseases and maternal and child health. However, there remains a significant knowledge gap about microfinance and Non-Communicable Diseases (NCDs). This review synthesises current evidence on microfinance and NCDs, including NCD-specific modifiable risks, health-seeking behaviour, and financing mechanisms of adults using microfinance services. Studies were identified through a systematic search of seven electronic databases, extracted for full-text screening, and analysed using a narrative analysis. A total of twelve articles that covered thirteen countries and four global regions were included in the review. Variations in study designs and reporting in the articles limited the ability to draw strong conclusions about microfinance and NCDs. However, the review revealed that microfinance may reduce modifiable risk factors, promote health-seeking behaviour, and reduce out-of-pocket health expenditure and catastrophic health expenditure related to NCDs. One study, however, found microfinance to be associated with negative effects of higher waist circumference, BMI and obesity rates. Overall, the review helped to identify the current gaps in knowledge, and highlighted the need to focus future research and publication on the use of microfinance to target NCDs of the poor.